1975
DOI: 10.1128/aem.29.3.317-322.1975
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Glutamic Acid in Aspergillus ochraceus During the Biosynthesis of Ochratoxin A

Abstract: The uptake and utilization of glutamic acid in the biosynthesis of ochratoxin A by Aspergillus ochraceus were studied. Uniformly labeled L-[YClglutamic acid was incorporated into both the phenylalanine and isocoumarin moieties of ochratoxin A. Penicillic acid was also labeled. During the early stages of development, the amino acid was used mainly for the synthesis of ribonucleic acid and protein. A portion of glutamic acid was oxidized and was recovered as metabolic 14CO2,. The initial uptake velocity of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This increased production of citrinin associated with a reduction of red pigments is actually in accordance with the fact that both metabolites aroused from the same metabolite precursors. This result is also in agreement with a previous work showing that glutamate and proline stimulated ochratoxin in Aspergillus ochraceus (Bacon and others 1975; Haggblom and Ghoch 1985). Also, proline has been described as positive effect on aflatoxin production in A. parasiticus and A. flavus (Payne and Hagler, 1983).…”
Section: Resultssupporting
confidence: 94%
“…This increased production of citrinin associated with a reduction of red pigments is actually in accordance with the fact that both metabolites aroused from the same metabolite precursors. This result is also in agreement with a previous work showing that glutamate and proline stimulated ochratoxin in Aspergillus ochraceus (Bacon and others 1975; Haggblom and Ghoch 1985). Also, proline has been described as positive effect on aflatoxin production in A. parasiticus and A. flavus (Payne and Hagler, 1983).…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, glutamic acid is incorporated in both the isocoumarin ring and phenylalanine of OTA by A . ochraceus [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira (6) reported that glutamic acid was indirectly involved in the production of ochratoxin A in shaken culture and that proline could be substituted. A study of the metabolism of glutamic acid during the production of ochratoxin A indicated that portions of it were incorporated into the mycotoxin (1). The production of F-2 followed an increase in pH of the medium, which may represent the deamination of glutamic acid.…”
Section: Concmentioning
confidence: 99%